El reconocimiento como hilo que teje eudaimonía (felicidad) y areté (virtud) (2011)
ABSTARCT: This paper approaches the issue of recognition from the standpoint of two contemporary European philosophers: Ricoeur and Honneth. Recognition is a means to recreate the horizons that become the possibilities to weave eudaimonía (happiness) and areté (virtue) into the social context, likewise, this can be the alternative before disdain as an experience of non-recognition that silences the other. Is the relationship with the others which is focused in self-acceptance, care for the others, self-validation, and recognition of the others in both the private and public domains, which can turn human experience into an experience of agape.